Effect of Solvents and pH Variation on Electronic Spectra of Dichloro-Nitroanilines - Yadav, B.S.; Yadav, M.K.; Kumar, Vipin; Singh, Vir (Asian Journal of Chemistry, 2010)
Electronic spectra in various polar solvents have been recorded in the region 2000 to 4000 Å. The effect of change of solvent on electronic transition of 2,4-dichloro-6-nitro- and 4,5-dichloro-2-nitroanilines is explained. The effect of pH variation has also been studied.